PERAN PARALEGAL DALAM MEMBERIKAN BANTUAN HUKUM - Zulaeha, Mulyani; Ariyani, Lies; Nurrosyifa Azzahra, Nabilla; Halim Sapoetra, Rahmat (Banua Law Review, 2023)
The state guarantees the constitutional rights of every person to obtain recognition, guarantees, protection and fair legal certainty as well as equal treatment before the law as a means of protecting human rights. The state's obligation to protect its citizens is based on the principles of Human Rights (HAM), one of which is fulfilling the right to legal assistance. Law 16 of 2011 concerning Legal Aid regulates the provision of legal aid by free legal aid providers for poor people throughout the territory of the Unitary State of the Republic of Indonesia (NKRI). Paralegal as a party who assists the Legal Aid Provider in implementing the provision of legal aid based on a letter of assignment, is supervised and evaluated by the Legal Aid Provider. The role of Paralegals in providing legal aid to the community is within the scope of non-litigation or out-of-court settlements limited to assisting Legal Aid Providers in providing legal aid to poor communities.